Persepsi Guru Pamong Terhadap Hubungan Sosial Mahasiswa PLK (Studi Terhadap Mahasiswa Jurusan Sejarah FIS UNP Periode Semester Genap Tahun Ajaran 2020-2021) - Yesi Annisa; Zafri Zafri (Jurnal Kronologi, 2021)
This research is motivated by the lack of social relations between PLK students majoring in history at FIS UNP for the even semester period of the 2020-2021 academic year. This study aims to describe the perception of civil servant teachers on the social relations of PLK students majoring in History of FIS UNP for the even semester period of the 2020-2021 academic year. This research is a descriptive research with quantitative data analysis with data collection techniques using questionnaires and descriptive statistical analysis with percentage counts. Based on the results of the study, it turned out that most of the perceptions of civil servant teachers on the social relations of PLK students in the History Department were positive (74%). The perception of civil servant teachers on the social relations of PLK students in the Department of History that is not good is related to the activities of PLK students in explaining things, creating and maintaining relationships with teachers, participating in various programs in the work environment and communicating the results of learning improvements with other teachers.